The Comparative Management Theory Jungle - Schöllhammer, Hans (Academy of Management Journal, 1969)
The proliferation of different conceptual approaches to comparative management theory makes it opportune to review, analyze, evaluate, and classify the various orientations, to examine the roots of this diversity and to propose a framework for synthesis.